Pragmatic Presupposition in Waspada Daily Articles - Umar Mono; Dian Marisha Putri; Liza Amalia Putri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
An article of editorial is the key of newspaper which is the editor’s point of view toward an actual event that is popular when it is published. The editor provides information such as events, incidents, facts or opinion so that readers know and understand it. The objectives of the research results are: Firstly, to describe kinds of presuppositions found in Waspada daily news. Secondly, out of all data, 6 articles or editorials, there are 201 sentences with presuppositions consisting of individual, existential, lexical, factive, structural, non-factive, and counter factive presupposotions. The data show that readers must have knowledge and situational context in order to make presupposition. The articles on Waspada daily news can be made teaching materials of Presupposition in Pragmatics. Among all speech acts, there is also a presupposition made by a speaker to the listener.